Mixed Finite Element Computation of Energy Release Rate in Anisotropic Materials Based on Virtual Crack Closure-Integral Method - Sami Derouiche; Salah Bouziane; HamoudiBouzerd Laboratory of Civil Engineering and Hydraulics, University of May 8, 1945, Guelma, Algeria. (Fracture and Structural Integrity)
The material with anisotropic properties are becoming widely essential due to the ease to manipulate their mechanical properties to obtain a particular quality, insure safety or a specific behavior. Those kinds of materials are considered anisotropic because their characteristics and behavior are dependent on every direction of the materials orientation. In this work, the virtual crack closure-integral technique is implemented to a mixed finite element, in addition to the stiffness derivative procedure, to evaluate the ERR of crack extension in anisotropic materials. A simulation of a cracked edge rectangular plate with anisotropic characteristics is taken for example. The results obtained are in good agreement with the analytical results, making the proposed technique a good model for fracture investigation and allow it to study more complicated cases in future works.